Migrant labour remittances : the developmental cycle and rural differentiation in a Lesotho community - Spiegel, Andrew David (Social Anthropology, 2016)
This dissertation addresses the problem of the impact of a migratory wage-labour system on relations of production and of distribution in rural Lesotho. Some 200 000 of that country's 1,25 million people are oscillating labour migrants to South Africa, most of them men. Their earnings, remitted to their rural home communities, provide the primary means of subsistence for their families and others left behind. The study focusses on the diffusion of remittances and the rural differentiation to which this is related. It is argued that such differentiation is closely associated with the cyclical process of domestic development in rural Lesotho. Data is presented to demonstrate how differentials in wealth correspond, to a large extent, with phases in the domestic developmental cycle. The strategies of homestead building, a clear indicator of domestic development, are described in order to point to the correspondence between differentiation and the developmental cycle. The more general process of regional class formation is also recognized. The interconnectedness of the local elite and the national bureaucracy, which together form an incipient petty bourgeoisie, demonstrates the effect of class formation at the local level. Remittances are seen to form the basis for economic activity which occurs in rural Lesotho communities. Agriculture, for example, is found to have as much a distributive function as a productive one insofar as co-operation provides an avenue for the diffusion of wage-earnings derived from outside productive activity. The material means of reproduction thus come primarily from involvement in the southern African industrial economy. It is concluded, therefore, that the process of incorporation has reached a point at which the people of Lesotho form a stratum of the regional working class, and it is suggested that this may also be the case for the residents of other peripheral labour exporting areas in southern Africa.